Sosialisasi Stop Tindakan Bullying dan Kekerasan Seksual di Sekolah SMAN X Kecamatan Y - Hendra Lukito; Mohamad Ikrom Arasid (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Education plays a fundamental role in shaping character, developing personality, and exploring students' potential. Schools should ideally be safe, comfortable, and conducive spaces for student growth and development. However, reality shows that the school environment is still vulnerable to negative behaviors such as bullying and sexual violence. Bullying is understood as aggressive behavior carried out repeatedly with the aim of harming the victim, whether through physical, verbal, social, or online media (cyberbullying). Meanwhile, sexual violence includes various forms of sexual acts without the victim's consent, which have serious impacts on psychological, social, and academic achievement. Sexual violence in schools not only harms the victims physically but also leaves deep psychological scars that may affect their future. To respond to this problem, KKM Group 30 Bina Bangsa University conducted a socialization activity entitled "Stop Bullying and Sexual Violence" at SMAN X, District Y. The main objective of this activity was to provide in-depth understanding, build awareness, and encourage mutual respect in the school environment. The outreach was conducted through several methods, including presentations by resource persons, educational drama performances depicting real-life cases, and interactive question-and-answer sessions involving active student participation. Interactive sessions are essential to engage students and encourage them to express their thoughts openly. The results of the activities demonstrated high student enthusiasm, increased understanding of the forms and impacts of bullying and sexual violence, and a growing awareness to report victims or witnesses. These activities emphasized that prevention is not solely the responsibility of schools but also requires collaboration between students, teachers, parents, and the wider community. This creates a safe, comfortable learning environment free from all forms of violence.